Spoken from the heart - Bush, Laura Welch, 1946- (Scribner, 2010)
In a captivating and compelling voice that ranks with many of the greatest memoirists, Laura Bush tells the story of her unique path from dusty Midland, Texas, to the world stage as First Lady. She captures presidential life in the frantic and fearful months after 9/11, and humorously lifts the curtain on what really happens inside the White House.